Adherence to quality indicators and surveillance guidelines in the management of Barrett’s esophagus: a retrospective analysis - Westerveld, Donevan; Khullar, Vikas; Mramba, Lazarus; Ayoub, Fares; Brar, Tony; Agarwal, Mitali; Forde, Justin; Chakraborty, Joydeep; Riverso, Michael; Perbtani, Yaseen B.; Gupte, Anand; Forsmark, Chris E.; Draganov, Peter; Yang, Dennis (Endoscopy International Open, 2018)
Background Adherence to quality indicators and surveillance guidelines in the management of Barrett’s esophagus (BE) promotes high-quality, cost-effective care. The aims of this study were (1) to evaluate adherence to standardized classification (Prague Criteria) and systematic (four-quadrant) biopsy protocol, (2) to identify predictors of practice patterns, and (3) to assess adherence to surveillance guidelines for non-dysplastic BE (NDBE).Methods This was a single-center retrospective study of esophagogastroduodenoscopy (EGD) performed for BE (June 2008 to December 2015). Patient demographics, procedure characteristics, and histology results were obtained from the procedure report-generating database and chart review. Adherence to Prague Criteria and systematic biopsies was based on operative report documentation. Multiple logistic regression analysis was performed to identify predictors of practice patterns. Guideline adherent surveillance EGD was defined as those performed within 6 months of the recommended 3- to 5-year interval.Results In total, 397 patients (66.5 % male; mean age 60.1 ± 12.5 years) had an index EGD during the study period. Adherence to Prague Criteria and systematic biopsies was 27.4 % and 24.1 %, respectively. Endoscopists who performed therapeutic interventions for BE were more likely to use the Prague Criteria (OR: 3.16; 95 %CI: 1.47 – 6.82; P < 0.01) than those who did not. Longer time in practice was positively associated with adherence to Prague Criteria (OR 1.07; 95 %CI: 1.02 – 1.12; P < 0.01) but with a lower likelihood of performing systematic biopsies (OR 0.91; 95 %CI: 0.85 – 0.97; P < 0.01). More than half (55.6 %) of patients with NDBE underwent surveillance EGD sooner (range 1 – 29 months) than the recommended interval.Conclusion Adherence to quality indicators and surveillance guidelines in BE is low. Operator characteristics, including experience with endoscopic therapy for BE and time in practice predicted practice pattern. Future efforts are needed to reduce variability in practice and promote high-value care.